POLITICS OF CRIMINAL LAW LIABILITY OF CORPORATE CRIMINAL IN INDONESIA - Hendriawan, Muhammad Rizaldi (YURIS: Journal of Court and Justice, 2022)
This research paper examines the urgent need to reform the Indonesian Criminal Code to recognize corporations as subjects of criminal law. It delves into the concept of corporate criminal liability, highlighting the importance of establishing clear legal frameworks to hold corporations accountable for their actions. The study analyzes the politics of criminal law in Indonesia, focusing on shaping legal policies to address societal needs and ensure justice. Key findings include the necessity of incorporating various theories of corporate punishment (such as strict liability, vicarious liability, identification theory, and aggregation theory) into the legal framework to effectively address corporate criminal behavior. The research also reviews the RKUHP (Revised Criminal Code Bill), which explicitly defines corporate criminal liability and outlines the responsibilities of corporate management in crimes committed on behalf of corporations. Using normative juridical research methods, including statute and conceptual approaches, the paper examines existing legal regulations and their implications for corporate accountability in Indonesia. Concluding that a comprehensive understanding of corporate criminal liability is vital for law enforcement and judicial authorities to enforce the law effectively, the study advocates for legal reforms aligned with the values of Pancasila, reflecting Indonesia's unique socio-cultural context while addressing the complexities of corporate crime.